건강자원자의 직장항문 생리검사에서 골반저 조율장애 진단의 위양성 결과에 대한 정신사회적 인자의 영향 - 송해정; Hae Jung Song; 이준성; Joon Seong Lee; 임희혁; Hee Hyuk Im; 홍수진; Su Jin Hong; 정인섭; In Seop Jeong; 조주영; Joo Young Cho; et al. (Journal of neurogastroenterology and motility, 2006)
목적: 정상인에서도 직장항문 생리검사 시 간혹 골반저 조율장애로 진단되는 위양성의 결과가 나온다. 본 연구의 목적은 건강자원자에서 직장항문 생리검사의 결과에 대한 정신사회경제적인 면이 미치는 영향에 대하여 알아보고자 하였다. 대상 및 방법: 40명의 건강자원자를 대상으로 전향적인 연구를 시행하였다. 모든 자원자들에게 정신건강상태 측정 및 개인력에 대하여 조사하고, 항문직장 내압검사, 풍선배출검사, 근전도 검사, 배변조영술, 대장통과시간을 측정하였다. 각 기능검사 결과로 골반저 조율장애를 진단함에 있어 정상군와 비정상군으로 나누어 각각의 정신사회적인 인자들을 비교분석하였다. 결과: 안정시와 압착시의 항문직장각의 차이가 15도 이하인 군과 15도를 초과하는 군을 비교하였을 때, 15도 이하인 군에서 신체화 점수가 더 높게 나타나는 경향을 보였으나 나머지 결과는 정신사회적 인자와는 차이가 없었다(p=0.092). 골반저 조율장애를 보인 군이 정상으로 관찰된 군에 비해 대학에 재학 중이거나 대학을 졸업한 사람들이 통계적으로 유의하게 더 많았다(p<0.05). 또한 골반저 조율장애를 보이는 군에서 정상으로 관찰되는 군에 비해 경제적인 여유가 있는 사람이 더 많았다(p<0.05) 결론: 항문직장 생리검사에서 정신건강적인 요인은 영향을 미치지 않을 것으로 생각하며 사회경제적인 요인은 배변조영술의 결과에 영향을 줄 수 있을 것으로 생각하나 이에 대해서는 더 연구가 필요하다. Background/Aims: False positive results are common in the diagnosis of pelvic floor dyssynergia (PFD) using anorectal physiologic studies (ARPS). The aim of this study was to determine the effects of psychosocial factors on false positive results of ARPS for the diagnosis of PFD in healthy volunteers. Methods: Forty healthy subjects were enrolled. All subjects underwent a complete self-rated inventory assessing psychological distress (SCL-90-R), personal history, anorectal manometry, balloon expulsion testing, electromyography, video-defecography and evaluation of colonic transit time. We compared a variety of psychosocial parameters between subjects with abnormal and normal results of the ARPS. Results: There was a tendency to have a more somatizing personality in subjects with changes in the anorectal angle less than 15 degrees during straining compared to subjects with a change in the anorectal angle more than 15 degrees (p=0.092). However, there were no other differences in psychosocial factors when compared to the results of the anorectal physiologic study. A group with suggestive pelvic floor dyssynergia by video-defecography had more college graduates than the normal group (p<0.05). Also, this group had a greater income than the normal group (p<0.05). Conclusions: Our findings suggest that psychological factors do not affect the results of ARPS. However, socioeconomic factors affect the results of defecography in the diagnosis of PFD in healthy subjects. (Kor J Neurogastroenterol Motil 2006;12:48-54)